Evidence for miR-548c-5p regulation of FOXC2 transcription through a distal genomic target site in human podocytes - Christofides, Andrea; Papagregoriou, Gregory; Dweep, Harsh; Makrides, Neoklis; Gretz, Norbert; Felekkis, Kyriacos; Deltas, Kōnstantinos (Cellular and molecular life sciences, 2020)
Podocytes are highly differentiated epithelial cells outlining the glomerular vessels. FOXC2 is a transcription factor essential for inducing podocyte differentiation, development and maturation, and is considered to be the earliest podocyte marker. miRNA prediction analysis revealed a full-length target site for the primate-specific miR-548c-5p at a genomic region > 8 kb upstream of FOXC2. We hypothesised that the transcription rates of FOXC2 during podocyte differentiation might be tuned by miR-548c-5p through this target site. Experiments were performed with cultured human podocytes, transfected with luciferase reporter constructs bearing this target site region within an enhancer element of the native plasmid. The results confirmed a seed region-driven targeting potential by the miRNA, with mimics downregulating and inhibitors enhancing luciferase activity. Introducing mutations into the miRNA target seed region abolished the expected response. In cultured podocytes, FOXC2 mRNA and protein levels responded to miR-548c-5p abundance in a coordinated manner before and after induction of differentiation, with high statistical significance. Ago-ChIP experiments revealed occupancy of the miRNA target site by miRNA/RISC in undifferentiated cells and its release when differentiation is initiated, allowing its interaction with the gene’s promoter region to amplify FOXC2 expression, as shown by chromosome conformation capture and qRT-PCR. Moreover, the expression pattern of FOXC2 during podocyte differentiation seems to be affected by miR-548c-5p, as removal of either endogenous or mimic miR-548c-5p results in increased FOXC2 protein levels and cells resembling those undergoing differentiation. Collectively, results indicate a well-orchestrated regulatory model of FOXC2 expression by a remote upstream target site for miR-548c-5p.
Published online: 17 September 2019
Gesehen am 05.10.2020